1993
DOI: 10.1021/ma00071a030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of poly(p-phenylene-cis-benzobisoxazole) in methanesulfonic acid

Abstract: Poly(p-phenylene-cis-benzobisoxazole) (cis-PBO) articles such as fibers possess exceptional mechanical strengths and moduli as well as high thermal performance and chemical resistance. These properties are assumed to be the result of the "rodlike" shape of this polymer. The intrinsic viscosity dependence on molecular weight (Mark-Houwink relationship) and the dependence of radius of gyration Rg with the degree of polymerization in methanesulfonic acid (MSA) solutions, however, suggest considerable deviations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 15 publications
(28 reference statements)
1
36
0
Order By: Relevance
“…The rotational freedom of PVP monomer units around -C-C-single bonds can provide a less-flexible chain [10,11,15]. We have tried to adjust our curve, by the second-order least-squares regression [13]. This adjustment is presented in Fig.…”
Section: Intrinsic Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…The rotational freedom of PVP monomer units around -C-C-single bonds can provide a less-flexible chain [10,11,15]. We have tried to adjust our curve, by the second-order least-squares regression [13]. This adjustment is presented in Fig.…”
Section: Intrinsic Viscositymentioning
confidence: 99%
“…In this article we also propose an equation, based on the second order least-squares regression, relating the intrinsic viscosity to the molecular mass of polymer as a special case to determine, in the other hand, the approximate values of MarkHouwink-Sakurada exponents [13]. Still, the motivation of this study came from the observation of difference between the molecular weight M w and "viscosity-average" molecular weight M η  , especially at higher masses [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is formed from a complex ring but the direction of the molecule is close to a straight line 1,2 . Therefore, the choice of a good solvent for the molecule is much limited for spinning and polyphosphoric acid is a reasonable choice for selecting a good solvent 3 .…”
Section: Introductionmentioning
confidence: 99%
“…To improve this mechanical properties much higher, we have been looking into the structural formation of fiber during coagulation and found that a non-aqueous coagulant gives a different fiber structure 1 . The fiber is expected to have a higher molecular orientation with less structural inhomogeneity along the fiber axis, which has been revealed by small and wide-angle X-ray diffraction (SAXS and WAXS) techniques and high-resolution transmission electron microscope (HREM) observation [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Figure 1 shows the relationship between fiber modulus and the crystallite orientation of the (200) diffraction of the PBO crystal estimated by X ray, in which the three fibers show high molecular orientation to the fiber axis than other conventional fibers 19 .…”
Section: Introductionmentioning
confidence: 99%